2007
DOI: 10.1007/s00244-006-0110-7
|View full text |Cite
|
Sign up to set email alerts
|

Contaminants in Lesser and Greater Scaup Staging on the Lower Great Lakes

Abstract: The decrease and subsequent lack of recovery of the North American scaup population has increased concerns about contaminants acquired during migration. We collected 189 fall- and spring-migrant lesser (Aythya affinis) and greater scaup (A. marila) on the lower Great Lakes (LGL) to determine if organic contaminants and trace elements in scaup livers were increased and to evaluate sources of variation in selenium (Se) burdens. We found that all organic contaminants were below toxic levels. Of 18 trace elements,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
16
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 44 publications
2
16
0
Order By: Relevance
“…Given these consistently low levels of contaminants in females and eggs across the breeding range of lesser scaup, it appears unlikely that females are importing deleterious levels of contaminants from wintering and spring staging areas and depurating those contaminants into their clutches. This is further corroborated by Petrie et al (2007) who recently found OC levels in spring staging scaup below thresholds known to cause reproductive impairment. However, earlier studies did detect elevated levels of OCs in lesser scaup on wintering and spring staging areas (Mazak et al 1997;Hothem et al 1998;Custer et al 2000).…”
Section: Discussionsupporting
confidence: 84%
“…Given these consistently low levels of contaminants in females and eggs across the breeding range of lesser scaup, it appears unlikely that females are importing deleterious levels of contaminants from wintering and spring staging areas and depurating those contaminants into their clutches. This is further corroborated by Petrie et al (2007) who recently found OC levels in spring staging scaup below thresholds known to cause reproductive impairment. However, earlier studies did detect elevated levels of OCs in lesser scaup on wintering and spring staging areas (Mazak et al 1997;Hothem et al 1998;Custer et al 2000).…”
Section: Discussionsupporting
confidence: 84%
“…Accumulation of toxicants may lead to mortality and sub-lethal effects such as altered growth, reproduction, and behaviour (Flemming and Trevors, 1989;Custer and Custer, 2000;Santore et al, 2002;Custer et al, 2003;Petrie et al, 2007). Metal accumulation has been implicated in many of these effects.…”
Section: Introductionmentioning
confidence: 99%
“…For example, cadmium transfer from zebra mussels to the tufted duck (Aythya fuligula) has resulted in behavioural disturbances in adults, growth retardation, and embryonic mortality (De Kock and Bowmer, 1993). Selenium toxicity impacts staging, winter body condition and health of lesser and greater scaup (Aythya affinis and Aythya marila), diving ducks that feed primarily on dreissenids (Custer and Custer, 2000;Custer et al, 2003;Petrie et al, 2007). Accumulation of copper may cause mortality and sub lethal effects such as altered growth, reproduction, and behaviour in fish and macroinvertebrate species (Flemming and Trevors, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…At the Great Lakes, selenium (Se) in livers of waterbirds is commonly recorded at concentrations considered increased [[10 lg g -1 dw (Heinz et al 1989;Heinz 1996)] or potentially harmful [[33 lg g -1 dw (Heinz et al 1989;Heinz 1996;Custer and Custer 2000;Petrie et al 2007;Schummer et al 2010Schummer et al , 2011]. However, Se also can decrease the toxicity of methylmercury (MeHg) through demethylation, whereby a nontoxic Hg-Se protein complex can be formed in the liver and kidneys (Stoewsand et al 1974;Heinz and Hoffman 1998;Eagle-Smith et al 2009).…”
mentioning
confidence: 98%
“…Inorganic contaminants continue to enter the Great Lakes through nonpoint sources and atmospheric deposition and are found in wildlife of the region at measurable and sometimes deleterious concentrations (Custer and Custer 2000;Evers et al 2005;Petrie et al 2007;Hogan et al 2007;Ware et al 2011). Common loons (Gavia immer) are aquatic, piscivorous, high-trophic level feeders and thus could be acquiring potentially harmful concentrations of contaminants either before arrival or during autumn staging on the Great Lakes (Krammar et al 2004).…”
mentioning
confidence: 99%